THE UNIVERSITY REFORM OF 1918: PAST, PRESENT AND FUTURE (Perspectivas de las Ciencias Económicas y Jurídicas, 2018)
The University Reform has been a historical landmark that corresponds to be remembered in every opportunity that presents itself. Here, close to the centenary of that event, it is analyzed in its historical, social and ideological aspects. In addition, we review the ideals that the students were vehemently defended and how they were adopted by the statute of our University, the National University of La Pampa.
Keywords: University reform; university extension; Córdoba movement; university co-government; free education